Financial Instruments of Economic Mechanisms for Strategic Development of Science and Education: Ecosystem Approach - M. A. Borovskaya; A. Yu. Nikitaeva; M. R. Bechvaya; O. A. Chernichenko (Финансы: теория и практика, 2022)
The authors substantiate the importance of choosing efficient financing instruments for the successful functioning of economic mechanisms that ensure the implementation of strategic priorities for economic development. The study shows that the spheres of science and education have a direct positive impact on the growth of the economy, being important priorities and drivers of economic development. Accordingly, it is necessary to develop clear strategic guidelines for the development of these areas and define financial instruments embedded in economic mechanisms to ensure their practical implementation. In this regard, the aim of the study is to conduct a retrospective analysis of science and education funding, considering international and domestic experience, to propose the conceptual content of sectoral strategies for the development of science and education at different levels of the economic hierarchy, and to identify financial instruments to ensure appropriate strategies. Based on the use of theoretical, empirical, comparative, institutional, and evolutionary analysis of international and domestic experience in science and education funding, the expediency of implementing an ecosystem approach to the development and funding of these areas is substantiated, which makes it possible to unite all interested participants in socio-economic ecosystems through partnerships and resource flows. The paper substantiates the importance of distinguishing between sectoral strategies for the development of science and education and suggests the content of the corresponding strategies at the macro-, meso-and micro-levels of the economy. The research contains a comprehensive analysis of the financing instruments and economic mechanisms for the development of science and education in Russia from 1992 to the present, taking into account their effectiveness.It also includes the study of new promising instruments for science and education. Based on the results of this analysis, the authors conclude that it is advisable to rely on those financing instruments that have a self-reproducing nature and allow forming the economy of science on the basis of the ecosystem approach and assume a balance of private and public funding.